A view upon environmental education in Saladeiro region, Quaraí- RS - Mazzuhy, Gisele de Castro (2015)
Given the relevance of Saladeiro neighborhood to the communities of Quaraí-RS and Artigas, Uruguay, it’s of great importance to the region a Bi-national Project that seeks to enhance environmental awareness actions in both countries. The proposed actions that may minimize the possible environmental and health problems caused by the accumulation of solid waste and stagnant water, allow an improvement in the quality of life of local people. The aim of this study was to survey the current perception of the surrounding residents and students from a public school in relation to environmental issues, to suggest proposals for improvement in the quality of the environment. The proposed actions consisted of lectures, educational folders and the proposal for the task force to clean the banks of the River Quaraí. Regarding the results obtained it was found that students and residents are aware of the environmental and health problems. It can be concluded that in relation to the perception of environmental problems both residents and students are aware of the problem and they understand that short, medium, or long term actions generate consequences, that is, if the environment is clean and healthy there won’t be disease vectors and it won’t be a factor that will collaborate with floods. From the improvement proposals, both residents and students are willing to cooperate with them, this being demonstrated through the interest in preserving the River Quaraí that had as proposal the cleaning of the banks that was not possible due to problems with dates available and the rains that wronged this activity, however, on the Uruguayan side the project was successful.